Neutrophil Extracellular Traps Induce Organ Damage during Experimental and Clinical Sepsis - Czaikoski, Paula Giselle; Mota, José Maurício Segundo Correia; Nascimento, Daniele Carvalho; Sônego, Fabiane; Castanheira, Fernanda Vargas e Silva; Melo, Paulo Henrique; Scortegagna, Gabriela Trentin; Silva, Rangel Leal; Barroso-Sousa, Romualdo; Souto, Fabrício Oliveira; Pazin-Filho, Antonio; Figueiredo, Florencio; et al. (PLOS ONE, 2016)
Organ dysfunction is a major concern in sepsis pathophysiology and contributes to its high mortality rate. Neutrophil extracellular traps (NETs) have been implicated in endothelial damage and take part in the pathogenesis of organ dysfunction in several conditions. NETs also have an important role in counteracting invading microorganisms during infection. The aim of this study was to evaluate systemic NETs formation, their participation in host bacterial clearance and their contribution to organ dysfunction in sepsis. C57Bl/6 mice were subjected to endotoxic shock or a polymicrobial sepsis model induced by cecal ligation and puncture (CLP). The involvement of cf-DNA/NETs in the physiopathology of sepsis was evaluated through NETs degradation by rhDNase. This treatment was also associated with a broad-spectrum antibiotic treatment (ertapenem) in mice after CLP. CLP or endotoxin administration induced a significant increase in the serum concentrations of NETs. The increase in CLP-induced NETs was sustained over a period of 3 to 24 h after surgery in mice and was not inhibited by the antibiotic treatment. Systemic rhDNase treatment reduced serum NETs and increased the bacterial load in non-antibiotic-treated septic mice. rhDNase plus antibiotics attenuated sepsis-induced organ damage and improved the survival rate. The correlation between the presence of NETs in peripheral blood and organ dysfunction was evaluated in 31 septic patients. Higher cf-DNA concentrations were detected in septic patients in comparison with healthy controls, and levels were correlated with sepsis severity and organ dysfunction. In conclusion, cf-DNA/NETs are formed during sepsis and are associated with sepsis severity. In the experimental setting, the degradation of NETs by rhDNase attenuates organ damage only when combined with antibiotics, confirming that NETs take part in sepsis pathogenesis. Altogether, our results suggest that NETs are important for host bacterial control and are relevant actors in the pathogenesis of sepsis.